Clinical evaluation of switching from immediate‐release to prolonged‐release lithium in bipolar patients, poorly tolerant to lithium immediate‐release treatment: A randomized clinical trial. Issue 3 (9th February 2022) - Pelacchi, Federica; Dell'Osso, Liliana; Bondi, Emi; Amore, Mario; Fagiolini, Andrea; Iazzetta, Paolo; Pierucci, Daniela; Gorini, Manuela; Quarchioni, Elisa; Comandini, Alessandro; Salvatori, Enrica; Cattaneo, Agnese; et al.
Abstract: Aim: The effect of switching from lithium immediate release (Li‐IR) to lithium prolonged release (Li‐PR) on lithium‐induced tremor after 1 and 12 weeks of treatment was evaluated in a randomized, multicenter, open trial, in bipolar patients from the participating sites with a tremor severity ≥2 (Udvalg for Kliniske Undersøgelser [UKU] rating scale) despite optimal lithium titration. Methods: The primary endpoint was the evaluation of tremor by means of the UKU scale after 1 week of treatment. Secondary endpoints included manic Young Mania Rating Scale (YMRS) and depressive symptoms (Montgomery–Asberg Depression Rating Scale), a global assessment of the patient's status (Clinical Global Impression), polyuria/polydipsia (UKU item 3.8) and patient‐reported outcomes. Results: Owing to difficulties in including suitable patients the enrollment phase was closed when 73 patients were randomized. Notwithstanding the lower number of patients, in the modified intention‐to‐treat population ( n  = 70) the primary endpoint was statistically significant: tremor improved after 1 week in 62.9% in Li‐PR group against 20.0% of patients in Li‐IR group ( p  = .0006; two‐tailed Fisher's exact test). The difference remained statistically significant after 4 ( p  = .0031) and 12 weeks ( p  = .0128). The same analysis performed in the PP population confirmed these results. Among the secondary endpoints, only the factor convenience of the treatment satisfaction questionnaire showed a statistically significant difference between groups. There were no apparent differences in the safety profile of the two formulations. Conclusions: This study is the first comparative documentation of a potential benefit of the prolonged‐release formulation in reducing the symptom tremor, a well‐known adverse effect of lithium therapy. Indeed, the study results should be interpreted taking into account the sample size lower than planned. Abstract : The effect of switching from lithium immediate release (Li‐IR) to lithium prolonged release (Li‐PR) on lithium‐induced tremor after 1 and 12 weeks of treatment was evaluated in a randomized, multicenter, open trial, in 70 bipolar patients with a tremor severity ≥2 (UKU rating scale) despite optimal lithium titration. After 1 week, switching tremor improved in 62.9% in Li‐PR group against 20.0% of patients in Li‐IR group ( p  = .0006; two‐tailed Fisher's exact test). The difference remained statistically significant after 4 ( p  = .0031) and 12 weeks ( p  = .0128).